Spark the brain, ignite the pen : quick writes for kindergarten through high school teachers and beyond - Totten, Samuel; Eaton, Helen; Dirst, Shelley; Lesieur, Clare (Emerald Publishing Limited : Information Age Publishing, 2009)
A NEW emphasis IN THIS edition of Spark the Brain, Ignite the Pen is writing to learn in the content areas. This edition of the work first published in 2006 includes a collection of classroom-tested quick writes designed to assist students in thinking and writing about significant content in the disciplines. Contributors to the book teach a wide array of grade levels (K through college) and subject areas e.g., English, social studies, math, science and health), and the quick writes included in the book are ideal for use in a variety of classroom subjects and settings.Given the current research validating the impact of using writing tasks to learn content, this volume should be useful to a wide range of teachers, teacher educators, and professional development trainers K-12.